Growth characteristics and grain yield of machine-transplanted medium indica hybrid rice with high daily yield - Fei DENG; Lian-hua HE; Duo CHEN; Chi ZHANG; Qing-lan TIAN; Zhen-yuan WU; Qiu-ping LI; Yu-ling ZENG; Xiao-yuan ZHONG; Hong CHEN; Li WANG; Wan-jun REN (Journal of Integrative Agriculture, 2022)
High-yield rice varieties with a suitable growth duration are required for mechanical transplanting in multiple cropping systems. Daily yield is an appropriate criterion for the selection of machine-transplanted rice varieties. The aim of this study was to investigate the growth characteristics and grain production in machine-transplanted medium indica hybrid rice with a high daily yield. We conducted a field experiment on 20 medium indica hybrid rice varieties in 2017 and 2018. Grain yield decreased significantly with growth duration between jointing and heading, but it increased with dry matter accumulation, growth rate between jointing and heading, dry matter partitioning to the stem plus sheath at heading, daily yield, and number of spikelets per panicle. Compared with the medium and low daily yield variety types, the high daily yield variety type increased shoot biomass by improving crop growth rate and dry matter accumulation amount between jointing and heading and after heading. The high daily yield variety type decreased the growth duration pre-heading and the proportions of dry matter partitioned to the leaf lamina at heading and maturity, but it also increased the post-heading accumulated dry matter in the grain and the remobilization of dry matter stored in the vegetative organs. Furthermore, the high daily yield variety type significantly increased the occurrence rate of tillers, which is beneficial for the formation of a larger panicle size and an increase in the grain-filling rate. These changes contributed to a 6.51–23.16% relative increase in grain yield of the high daily yield variety type. In conclusion, the selection of high daily yield indica hybrid rice varieties with shorter pre-heading growth duration, greater tiller occurrence rate and spikelet numbers per panicle, higher post-jointing growth rates and stem plus sheath dry matter accumulation at heading is suitable for machine-transplanted rice.